Petrogenesis and tectonic setting of Early Cretaceous granodioritic porphyry from the giant Rongna porphyry Cu deposit, central Tibet - Zhang, X.; Li, G.; Qin, K.; Lehmann, B.; Li, J.; Zhao, J.; Cao, Mingjian; Zou, X. (Pergamon-Elsevier Science Ltd, 2018)
© 2018 The Rongna Cu-(Au) deposit is a recently discovered giant low-grade composite porphyry-high sulfidation epithermal system in the Duolong ore district of central Tibet. We present zircon U-Pb ages, bulk-rock geochemical and Sr-Nd isotope data, as well as zircon Hf-O isotope data to constrain the petrogenesis of the Rongna granodioritic porphyry, on which the ore system is centered. Secondary ion mass spectrometry (SIMS) zircon U-Pb data for two samples yielded ages of 118.7 ± 0.9 Ma and 117.1 ± 0.9 Ma, respectively. The granodioritic porphyry is of high-K calc-alkaline and magnetite-series affinity, with enrichment of light rare earth elements (LREEs) and large-ion lithophile elements (e.g., Rb, Pb, and K), and depletion of high-field strength elements (e.g., Ta, Nb, and Ti), typical of the geochemical signature of arc magmas. The Rongna granodioritic porphyry has initial Sr isotopic ratios of 0.7060–0.7099, and eNd(t) values of -5.7 to -1.7 with TDM(Nd) of 983–1900 Ma. The zircons have relatively narrow Hf-O isotopic compositions (eHf(t) = +3.30– +6.43; d18O = +5.94– +6.96‰), indicating the involvement of old crustal materials. Our data suggest that the Rongna granodioritic porphyry likely evolved by fractional crystallization from a hybrid magma of mantle-derived mafic melts and lower crustal felsic melts during a period of magmatic flare-up following flat-slab subduction.